2017
DOI: 10.1021/acsami.6b14650
|View full text |Cite
|
Sign up to set email alerts
|

Macrofibers with High Mechanical Performance Based on Aligned Bacterial Cellulose Nanofibers

Abstract: Bacterial cellulose (BC) nanofibers represent an emerging class of highly crystalline bionanofibers with high intrinsic mechanical properties. The remarkable nanofibers with oriented structure and strong interfibrillar interactions can realize high-performance materials. In this study, we demonstrated that macrofibers based on aligned BC nanofibers could be prepared by wet spinning and drawing procedures. The relationship between process conditions, structure, and mechanical properties of macrofibers were inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
170
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(175 citation statements)
references
References 52 publications
4
170
1
Order By: Relevance
“…Compared with other studies on high-performance nanocellulose-based materials with anisotropic structure as shown inFigure 6c,19,36,[58][59][60][61][62][63][64][65][66][67][68][69][70] our aligned P0.1TOCNF-g-PEG exhibits competitive ultimate strength and superior toughness with only 0.1 wt% of nanocellulose, indicating a promising future of utilizing this kind of materials in low-cost and environment-friendly applications.However, it needs to be noted that there is no significant difference in the elastic modulus of the aligned samples as illustrated inFigure 6b. This indicates that the elastic modulus of the aligned PLA-based nanocomposites with such a low fraction of reinforcement is mainly controlled by the alignment and crystallization of PLA chains.…”
mentioning
confidence: 78%
“…Compared with other studies on high-performance nanocellulose-based materials with anisotropic structure as shown inFigure 6c,19,36,[58][59][60][61][62][63][64][65][66][67][68][69][70] our aligned P0.1TOCNF-g-PEG exhibits competitive ultimate strength and superior toughness with only 0.1 wt% of nanocellulose, indicating a promising future of utilizing this kind of materials in low-cost and environment-friendly applications.However, it needs to be noted that there is no significant difference in the elastic modulus of the aligned samples as illustrated inFigure 6b. This indicates that the elastic modulus of the aligned PLA-based nanocomposites with such a low fraction of reinforcement is mainly controlled by the alignment and crystallization of PLA chains.…”
mentioning
confidence: 78%
“…After 1 min later, NaClO (7.8 mL) was immediately added to the suspension. Oxidation time was 1 h and pH was 10.5 at room temperature (Yao et al 2017 ). The OBC was dialyzed in distilled water for 1 week and concentrated to 7 wt% by centrifuging at 12,000 rpm for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Deconvolution of the amide I band in a single spectra provided an estimation of 22% ± 2.6% β‐sheet content, 76% ± 3.2% random coil/α‐helix, and 2.0% ± 1.3% β‐turn, respectively (Figure 3C and Table 2 ). It was demonstrated that stretching and shear force could further improve the mechanical properties through improvement of fibril alignment or ionic crosslinking,33–35 which also occurred in the spinning of spider silk 36. Thus, a 5% strain was performed to study structural response of the silk fiber.…”
Section: Species D [µM] Young's Modulus [Gpa] Strength [Mpa] Strain [mentioning
confidence: 99%